Occurrence of a single-species cyanobacterial bloom in a lake in Cyprus: monitoring and treatment with hydrogen peroxide-releasing granules - Keliri, Eleni; Paraskeva, Christia; Sofokleous, Angelos; Sukenik, Assaf; Dziga, Dariusz; Chernova, Ekaterina; Brient, Luc; Antoniou, Maria G. (My University, 2021)
Background: Excess loads of nutrients finding their way into waterbodies can cause rapid and excessive growth of phytoplankton species and lead to the formation of cyanobacterial harmful algal blooms (cyano-HABs). Toxic cyanobacteria produce a broad range of bioactive metabolites, some of which are known as cyanotoxins. These metabolites can negatively impact the ecosystem, and human and animal health, thus their presence needs to be closely monitored and mitigated. This study aimed to monitor St. George Lake (Athalassa National Forest Park, Cyprus) for its water quality characteristics, and initiate a new methodology to control the bloom that occurred in the lake during summer 2019, by comparing hydrogen peroxide treatment with novel metallic peroxide granules as source of hydrogen peroxide. Results: Lake monitoring showed that pH, salinity, total dissolved solids and conductivity varied throughout the year, and nutrients concentration was high, indicating a eutrophic lake. The cyanobacterium Merismopedia sp. bloomed in the lake between June and September 2019, comprising up to 99% of the phytoplankton biovolume. The presence of microcystin synthase encoding gene (mcyB, mcyE) was documented, however microcystins were not detected by tandem mass spectroscopy. Treatment with liquid hydrogen peroxide in concentrations 1 to 5 mg L−1 had no effect on the phycocyanin fluorescence (Ft) and quantum yield of PSII (Fv/Fm) indicating an ineffective treatment for the dense Merismopedia bloom (1 million cells mL−1 ± 20%). Metallic peroxide granules tested for their H2O2 releasing capacity in St. George Lake water, showing that CaO2 released higher H2O2 concentration and therefore have better mitigation efficiency than MgO2 granules. Conclusion: The present study highlights the importance of monitoring several water parameters to conclude on the different actions to be taken to limit eutrophication in the catchment area. The findings demonstrated that testing for the presence of genes involved in cyanotoxin production may not be sufficient to follow cyanotoxins in the water, therefore it should be accompanied with analytical confirmation. Treatment experiments indicated that slow release of H2O2 from peroxide granules may be an alternative to liquid hydrogen peroxide when applied in appropriate doses, but further investigation is needed before it is applied at the field.
Keywords: Cyanobacteria; Granules; Hydrogen peroxide; Merismopedia sp.; Monitoring; Nutrients; Treatment; Water quality